2020
DOI: 10.1177/0333102420942220
|View full text |Cite
|
Sign up to set email alerts
|

Very young age of onset in trigemino-autonomic cephalalgias – case report and review of the literature

Abstract: Background Trigemino-autonomic cephalalgias are very rare disorders and even rarer in children and adolescents. We report the onset of paroxysmal hemicrania in a very young girl and reviewed the scientific literature for similar cases. Findings We describe the case of a 1.6-year-old girl with left-sided headache attacks fulfilling the criteria of paroxysmal hemicrania including prompt responsiveness to indomethacin. In addition, we detected at least two children for every trigemino-autonomic cephalalgias subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…A total of 182 records were identi ed and reduced to 116 after removing duplicates. After screening and the application of the eligibility criteria, 22 articles (10,11,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) met the inclusion criteria. Figure 1 presents the ow diagram of included and excluded articles of our review according to PRISMA (41).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 182 records were identi ed and reduced to 116 after removing duplicates. After screening and the application of the eligibility criteria, 22 articles (10,11,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) met the inclusion criteria. Figure 1 presents the ow diagram of included and excluded articles of our review according to PRISMA (41).…”
Section: Resultsmentioning
confidence: 99%
“…Among previous studies in the pediatric population, CPH, EPH, and not-speci ed-PH were reported in 23, 7, and 5 patients, respectively. PH has been described among children and adolescents in various parts of the world including the United States (USA) (10,23,27,35), Canada (29,39), United Kingdom (UK) (21), Germany (22,25,30,31), France (40), Italy (26, 32, 38), Austria (34), Estonia (36, 37), Brazil (24), Portugal (11), Japan (28), and Korea (33), but the races were not speci ed in most of the studies. Unless one study, the gender of all cases was reported (10).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations